Iron limitation enhances acyl homoserine lactone (AHL) production and biofilm formation in clinical isolates of Acinetobacter baumannii - Modarresi, Farzan (Virulence, 2015)
Acinetobacter baumannii is an important source of infections in intensive care units (ICUs) of our hospitals in Kerman, Iran and the most frequently isolated strains produce biofilm. There is a little information about role of iron (Fe) levels on acyl homoserine lactone (AHL) production and biofilm formation in this microorganism. In the present study, we investigated the influence of iron-III limitation on AHL, siderophore, catechol and virulence factors in the biofilm forming clinical strains of A. baumannii. A total of 65 non-duplicated multidrug resistance (MDR) strains of A. baumannii were isolated from patients in ICUs of 2 hospitals in Kerman, Iran. Antibiotic susceptibility, siderophore and other iron chelators, hemolysis, cell twitching motility, capsule, gelatinase and DNase were studied. Presence of quorum sensing, LuxI and LuxR genes was detected by multiplex-PCR. AHL activity quantified by colorimetric method and the functional groups were determined by Fourier Transform Infra-Red Spectroscopy (FT-IR). Biofilm formation was detected by microtiter plate technique. All of the isolates were resistant to third generation of cephalosporins, ciprofloxacin, levofloxacin, tetracycline, whereas, 78% and 81% were resistant to amikacin and carbapenems, respectively. The siderophore activity was highest at 20 μM Fe(3+) (70%); however, it decreased to 45% as concentration of Fe(3+) increased to 80 μM. Furthermore, screening of the isolates for LuxI and LuxR genes showed that presence of both genes required in the isolates with high AHL activity. FT-IR analysis indicated C=O bond of the lactone ring and primary amides. Significantly, a higher amount of AHL (70%) was detected in the presence of low concentration of iron-III (20 μM); as iron concentration increased to 80 μM, the AHL activity was reduced to 40% (P ≤ 0.05). All the isolates exhibited twitching motility and had a capsule. No any gelatinase or DNase activity was detected. Quantification of the biofilm formation introduced 23 isolates with efficient attachment to microplate wells and strong biofilm. We found that both the AHL production and biofilm formation were regulated by iron concentration in a dose dependent manner. These findings provide evidence that iron limitation plays an important regulatory role in AHL and siderophore production resulting in strong or weak biofilm, thereby helping the organism to persist in less available micronutrient environment.